Decoding article 6 of the Paris agreement. (Asian Development Bank, 2018)
Article 6 is a key part of the Paris Agreement. It allows Parties to voluntarily cooperate to meet their Nationally Determined Contributions, providing for international transfers of mitigation outcomes, a new mechanism for mitigation and sustainable development, and non-market approaches. Article 6 establishes the foundation for a post 2020 carbon market, but there are still many complex issues to be discussed and decided among Parties to finalize the Paris Agreement rulebook by the end of 2018. This publication examines the options for establishing guidance, rules, and modalities for the key elements of Article 6, decoding issues such as internationally transferred mitigation outcomes, environmental integrity, double counting and corresponding adjustments.